High Diversity, Prevalence, and Co-infection Rates of Tick-Borne Pathogens in Ticks and Wildlife Hosts in an Urban Area in Romania - Borşan, Silvia-Diana; Ionică, Angela Monica; Galon, Clémence; Toma-Naic, Andra; Peştean, Cosmin; Sándor, Attila D.; Moutailler, Sara; Mihalca, Andrei Daniel (Frontiers in Microbiology, 2021)
Despite the increasingly recognized eco-epidemiological importance of ticks as vectors for numerous zoonotic pathogens in urban areas, data regarding the pathogen diversity and co-infection rates in ticks and wildlife hosts in urban and peri-urban Romania are scanty. We aimed to establish the risk of human exposure to co-infected ticks in Cluj-Napoca, a major city in Romania. DNA was isolated from 151 questing ticks: Ixodes ricinus (n=95), Haemaphysalis punctata (n=53), Dermacentor reticulatus (n=2), and Dermacentor marginatus (n=1); 222 engorged ticks: I. ricinus (n=164), I. hexagonus (n=36), H. punctata (n=16), H. concinna (n=6), and 70 tissue samples collected from wildlife hosts during 2018 in five urban, and two peri-urban sites. Using a pre-designed Fluidigm real-time PCR dynamic array, all DNA samples were individually screened for the presence of 44 vector-borne pathogens. Subsequently, conventional PCRs were performed for a selection of samples to allow validation and sequencing. In total, 15 pathogens were identified to species and 6 to genus level. In questing ticks, single infections were more common than co-infections. Seven Borrelia spp. were detected in questing I. ricinus, and three in H. punctata ticks. An overall high prevalence and diversity of Borrelia burgdorferi sensu lato was seen in urban questing ticks. Other pathogens of the order Rickettsiales were present with variable prevalence. Co-infections occurred in 27.4% (95% CI: 18.72-37.48) of all infected questing ticks. In engorged ticks the overall Bo. burgdorferi sensu lato prevalence was 35.6% (95% CI: 29.29-42.27), with five species present. Pathogens of the order Rickettsiales were also frequently detected. We report for the first time in Romania the presence of Rickettsia aeschlimannii and Rickettsia felis. Overall, from the infected engorged ticks, 70.7% showcased co-infections. In Ixodes spp., dual co-infections, namely Borrelia spp. and Anaplasma phagocytophilum, and Rickettsia helvetica and A. phagocytophilum were the most prevalent. Given the outcome, we underline the need to establish proper tick-surveillance programs in cities and include co-infections in the management plan of tick-borne diseases in Romania.